ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LOAN TO DEPOSIT RATIO (STUDI pada 10 BANK TERBESAR DI INDONESIA PERIODE 2014) - Syafi’i, Muchammad (Jurnal Ilmiah Mahasiswa FEB, 2014)
The aim of this study was to anlyze the factors that effect the succes of intermediation include capital, bank size, assets quality, operating expense, and net open position. The method used is descriptive with secondary data from financial statements 10 bank as a research object units. Data analysis technique is the panel regression, hypothesis testing while using t-test to examine the effect of partial variables and test-F to examine the effect of variables    simultaneosly with a significant level of 5%.  Based on the results it is concluded that partial CAR, SIZE, KAP, BOPO significant effect on LDR. While the PDN has effect not significant to LDR. Simultaneously, all independent variables significantly influence the level of influence of LDR.Keywords : LDR, CAR, SIZE, KAP, BOPO, PDN